Supervised Exercise Interventions in Childhood Cancer Survivors: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Qing Shi; Junyi Zheng; Ke Liu (MDPI AG, 2022)
Background: Childhood cancer survivors (CCSs) may suffer from a multitude of health impairments, resulting in a compromised quality of life (QoL). This review's objective was to examine CCSs' adherence to supervised exercise training interventions and the impact of these interventions on health outcomes. Methods: The following databases were searched in May 2022: PubMed, Embase, Cochrane Library, and Web of Science. The included studies were limited to randomized controlled trials (RCTs), published in English involving CCSs aged 18 years and below. Results: Nine RCTs (n = 642 participants) were included in the systematic review, and seven of them (n = 551 participants) were included in the meta-analysis. Both the mean retention rate and adherence to the supervised exercise interventions were 87%. Supervised exercise interventions significantly improved muscle strength (standardized mean difference (SMD) = 1.42, p = 0.03), level of daily physical activity (SMD = 1.05, p < 0.001), body mass index (BMI) (mean difference (MD) = 1.06, p = 0.03), and fatigue (SMD = −0.44, p < 0.001), while there was no statistical significance in the quality of life (QoL) (SMD = 0.21, p = 0.20). Conclusions: The adherence of CCSs to supervised exercise interventions is high, and supervised exercise interventions are safe and effective.